The Management of Zakat and Waqf in the Economic Development Efforts of Aljazair - Maryam Batubara; Sibral Malasyi (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2024)
This article discusses zakat management in Aljazair, focusing on changes in zakat management plans, the history of Zakat, and mechanisms for collecting and distributing zakat funds. Aljazair is facing changes in zakat management with plans to establish a National Zakat Council, in response to public dissatisfaction with the existing system. The history of Zakat in Aljazair reflects its critical role before the colonial era, but experienced significant decline during that period. Zakat management in Aljazair involves Kotak Zakat as a voluntary organization with strategic partnerships, innovation in utilizing Zakat, and the use of technology to increase efficiency and transparency. The distribution of zakat funds involves an application process from mosque units, which the Regional Council supervises. Partnerships with financial institutions such as Bank Al-Barakah Aljazair create innovative solutions such as the Zakat Investment Box. Through an organized approach and strategic partnerships, Zakat management in Aljazair is committed to utilizing Zakat for social welfare. In the management of Zakat and waqf in Aljazair, it can be concluded that there are 48 directorates of religious affairs and waqf located in each of the 48 provinces in Aljazair. They are considered a scaled-down version of the ministries of religious affairs and endowments, where they have small offices and departments representing specific tasks assigned by the ministry. They oversee the management of zakat funds, waqf assets, Hajj and Umrah affairs and other religious affairs in each of the country's 48 provinces. Each religious and waqf directorate has a separate department dedicated to waqf asset collection, dispute management, and investment. All religious and waqf directorates are directly related to the central directorate in the capital and the ministry of religion and waqf.